Analytics for Protecting Critical Infrastructure - Zagorecki, Adam; Ristvej, Jozef; Klupa, Krzysztof (Communications - Scientific letters of the University of Zilina, 2015)
In this paper we review the key trends related to application of information technology and, in particular, automated data analysis to the problem of protecting critical infrastructure. We focus on technologies that use automated data collection and analyses that can be exploited for improving security provision for critical infrastructure in the future. Of our particular interest are technologies that are at relatively early stage of adaptation and in our judgement have potential to significantly affect how the security is provided in the future, the technologies that support physical aspect of security. Then we discuss analytics in context of cyber-security with applications.